Anthropogenic and background components of the underwater acoustic environment in the Baltic Sea - Syrjälä, Joonas (fi=Turun yliopisto|en=University of Turku|, 2018)
Underwater acoustic environment has always been full of sounds due to natural sound sources, such as breaking waves or cracking ice. The acoustic environment, however, has changed in the last centuries as anthropogenic noise has been introduced. Shipping is the most pervasive source of underwater noise that dominates the low frequencies of the marine environment due to long-range propagation of underwater sound. Transient vessel traffic also generates local in-termittent noise peaks. This noise has multiple detrimental impacts on a large variety of marine species. Although underwater noise has been recognized as an environmental issue, there are still large knowledge gaps in understanding the full extent of the impacts especially in the shal-low, brackish water environment of the Baltic Sea. This study focused on the separation of anthropogenic intermittent noise from the dynamic background noise in four locations at the Estonian coast in the Baltic Sea using an adaptive threshold level technique. The source for the intermittent noise was validated with Automatic Identification System (AIS) data depicting nearby vessel traffic. The source for background noise was compared to the sea-state, wind and precipitation. These anthropogenic and intermittent components of the acoustic environment were characterized and compared with sound expo-sure level (SEL) in three 1/3 octave bands. The anthropogenic intermittent noise can be separated with the adaptive threshold technique in the Baltic Sea and vessel traffic can be identified as the primary source of intermittent noise. The background noise varies spatially and can be explained by environmental factors in certain locations. The intermittent noise dominates the total acoustic environment near shipping lanes and elevates SEL by 20 – 30 dB in the 63 Hz 1/3 octave band, by 13 – 22 dB in the 125 Hz band and by 5 – 8 dB in the 2000 Hz band.